Reuse Of Djenane Abd-El-Tif, An Emblematic Islamic Garden In Algiers - Hocine, Malika; Chemrouk, Naima Chabbi (Journal of Islamic Architecture, 2015)
Djenane Abd-el-Tif is an example of an Algerian summer residence dating from the Ottoman era. This type of building is not very well-known and remains marginalized in research that is more interested in the townhouses of the medina of Algiers. Yet, the gardens, the ingenious irrigation systems, fountains, and other patterns of Islamic gardens make of these djenane a unique typology worth exploring and preserving. Indeed, Islamic garden design is an art in itself and any restoration or conservation work should preserve the authenticity of its characteristics. The djenane Abd-el-Tif was fully restored following the damage caused by the Boumerdès earthquake in 2003. This led to the discovery of various elements that are particularly informative about its architecture and composition. It also highlighted the existence of valuable Islamic garden patterns, together with the djenane’s exceptional flora, which could provide added-value to the tourism potential of such residences. However, if restoration work has saved the djenane Abd-el-Tif, its garden with its Islamic design characteristics is not yet fully investigated nor listed as a cultural heritage. This article presents the djenane as a cultural heritage and argues that right restoration and reuse could contribute to enhancing knowledge about Islamic garden design in North Africa.